Hubungan Antara Gaya Belajar Terhadap Prestasi Belajar Matematika Kelas VIII MTs Negeri 1 Baubau - Risna Karim; Anwar Anwar; Ernawati Jais (Jurnal Akademik Pendidikan Matematika, 2023)
The formulation of the problem in this study was is there a relationship between learning styles and mathematics learning achievement of clas VIII MTs Negeri 1 Baubau students? The purpose of this study was to determine the relationship between learning style and mathematics achievement in clas VIII MTs Negeri 1 Baubau. This study used ex post facto research with quantitative methods. The population in this study were all class VIII students of MTs Negeri 1 Baubau for the Academic Year 2021/2022 which consisted of 7 study groups, namely 239 students. The sampling technique used random sampling technique, taken at least 36% of the entire sample and taken as many as 86 students. The data collection in this study is in the form of a questionnaire on learning styles and students’ learning achievement in mathematics obtained from  the grade VIII student report cards of MTs Negeri 1 Baubau in the even semester of the 2021/2022 academic year. The data analysis used to test the hypothesis were simple regression and correlation analysis. Bsed on the results of the analysis using simple regression, the linear regression equation was obtained: Y = 61,937 + 0,237X, with a t value of 3.732, significant at 0.000 <0.05. this has shown that  is accepted or  is rejected, which means that there is a positive relationship between learning style and mathematics achievement for clas VIII MTs Negeri 1 Baubau.